2020
DOI: 10.1097/bpo.0000000000001518
|View full text |Cite
|
Sign up to set email alerts
|

Open Reduction of Neglected Supracondylar Humeral Fractures With Callus Formation in Children

Abstract: Background: The standard treatment for supracondylar humeral fractures (SHFs) in children is closed reduction and percutaneous Kirschner (K)-wire fixation. In patients who present >14 days after injury and show callus formation, this procedure cannot be performed. There are 2 options in these cases: functional exercises with osteotomy performed at a later stage if cubitus varus is present, or immediate open reduction and percutaneous K-wire fixation. This study aimed to evaluate the outcomes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…ROM flexion-extension of the elbow is very important in daily living activities. Limitations of these ROM tend to decrease quality of life, especially in flexion [7]. All of the patients in this case series had increases in flexion ROM and also decreased lag extension after early reconstructive surgery.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…ROM flexion-extension of the elbow is very important in daily living activities. Limitations of these ROM tend to decrease quality of life, especially in flexion [7]. All of the patients in this case series had increases in flexion ROM and also decreased lag extension after early reconstructive surgery.…”
Section: Discussionmentioning
confidence: 63%
“…Displaced supracondylar humeral fractures are injuries that are difficult to treat and require procedures that are more difficult technically for orthopedic experts [4], [5], [6]. Supracondylar humeral fractures are usually treated in an acute state in pediatric patients [7]. Standard management for this fracture in children is through closed or open reduction and fixation by Kirshner (K)-wire.…”
Section: Introductionmentioning
confidence: 99%
“…The overall rate of complications after CRPP in type III fractures is approximately 8% [32]. [17] is the standard treatment and at the same time treatment options preferred by most surgeons for grade II and III supracondylar fractures with operative indication [16] [33][34][35]. After blind percutaneous pinning, satisfactory results are obtained in 98% of cases.…”
Section: Therapeutic Options In Common Formsmentioning
confidence: 99%
“…During the rst 14-60 days the hypertrophic callus can be peeled off. Evaluation of the results in children with SHF operated after 14 days by previous approach, analyzing the Bauman angle, K-wires con guration, carrying angles, Mayo Elbow performance score and Flynn criteria showed that the distant results are poor [16].…”
Section: Neglected Fractures Treated By Open Reduction After 14-60 Damentioning
confidence: 99%
“…During the first 14-60 days the hypertrophic callus can be peeled off. Evaluation of the results in children with SHF operated after 14 days by previous approach, analyzing the Bauman angle, K-wires configuration, carrying angles, Mayo Elbow performance score and Flynn criteria showed that the distant results are poor [16]. Lateral, medial or double approach (both lateral and medial), rigorous and non-aggressive dissection, pinning in "double X" without immobilization with rapid resumption of elbow mobility allows recovery of elbow mobility and reduces recovery period that can reach one year after immobilization in plaster cast [17].…”
Section: Neglected Fractures Treated By Open Reduction After 14-60 Days From Onsetmentioning
confidence: 99%